An ultra-low power, reconfigurable, aging resilient RO PUF for IoT applications. (October 2019) - Khan, Sajid; Shah, Ambika Prasad; Gupta, Neha; Chouhan, Shailesh Singh; Pandey, Jai Gopal; Vishvakarma, Santosh Kumar
Abstract: Physically Unclonable Functions (PUF) have emerged as security primitives which can generate high entropy, temper resilient bits for security applications. However, the power budget of the ring oscillator (RO) PUF limits the use of RO PUF in IoT applications, in this concern a low power variant of RO PUF is much needed. In this paper, we have presented an ultra-low power, lightweight, configurable RO PUF based on the 4T XOR architecture. The proposed architecture is aging resilient; hence it produces a stable PUF output over the years. Also, it has a large number of challenge-response-pair (CRP) compared to the other architectures, which makes it suitable for chip identification as well as cryptographic key generation. The proposed PUF is implemented on 40 nm CMOS technology, and for the validation of design, we have also implemented on FPGA. The simulation results show that it has a uniqueness of 0.489 and worst-case reliability of 96.43% and 93.15% at 125 °C and 1.2 V, respectively. Compared to the conventional RO PUF it consumes 98.06% and 95.47% less dynamic and leakage power, respectively.